The Concepts of Gamification Profiling to Generate Smart City Maturity Level Mapping & Social Profiling (Smart Society) - Gamayanto, Indra; Maulana, Herman Try; Sirait, Tamsir Hasudungan; Prasetyo, Lusi Noviani (IJISTECH (International Journal of Information System and Technology), 2023)
Gamification is an extraordinary phenomenon of how we can engage users to understand our Business. Users can get many interesting things from gamification offered by business owners, ranging from games, bonuses, discounts, and many other things that can make users or consumers more loyal and have a close relationship with the Business. This research is developing the concept of innovation profiling, which describes seven types of innovation. Here, gamification is one of the innovations we will discuss. This study divides gamification into three important parts, units that should not be separated. The first part concerns the big picture of gamification profiling and the Formula GMF = P. B2. E2. Ps2.F2. In the second stage, there are four types of gamification- open Gamification (OP), specific Gamification (SG), innovative Gamification (IG), and undeveloped Gamification (UG). The third stage, the final stage, is Business Gamification profiling (BG), Education gamification profiling (EG), Psychology gamification profiling (PG), and Future gamification profiling (FG). This research results in the gamification profiling framework and its application in education as the main case study in implementing this. Furthermore, Smart city and social profiling are two things that cannot separate from each other. Therefore, in building a smart city & social profiling, several important things must be considered, including investors, people, culture, supervision, customers, data, mapping, mentors, capabilities, commercials and leadership. This article will develop Business Model Mapping 101 (Smart City Maturity Level Mapping), an innovation in shaping and producing social profiling. Problems such as implementing smart cities in human resources, technology, and other factors are the main concerns. Therefore, Smart City Maturity Level Mapping is a social profiling development concept that focuses on building something from what the area already has. It is to increase the level of a more stable economy but remain flexible in dealing with certain situations. Furthermore, this article complements the previous article, namely smart city 5.0 (Human resource, Technology, marketing). These three things then developed into Smart City Maturity Level Mapping, which later became social profiling, which is useful for measuring smart cities' performance and implementation in a more structured, systematic and detailed manner in terms of profiles. The final result is the maturity level to measure a smart city's performance, which also connected to the defender, extender, dodger, contender.